Acute Cannabigerol Administration Lowers Blood Pressure in Mice - Vernail, Victoria L.; Bingaman, Sarah S.; Silberman, Yuval; Raup-Konsavage, Wesley M.; Vrana, Kent E.; Arnold, Amy C. (Frontiers in Physiology, 2022)
Cannabigerol is a cannabinoid compound synthesized by Cannabis sativa, which in its acid form acts as the substrate for both delta-9-tetraydrocannabinol and cannabidiol formation. Given its lack of psychoactive effects, emerging research has focused on cannabigerol as a potential therapeutic for health conditions including algesia, epilepsy, anxiety, and cancer. While cannabigerol can bind to classical cannabinoid receptors, it is also an agonist at alpha2-adrenoreceptors (alpha2AR) which, when activated, inhibit presynaptic norepinephrine release. This raises the possibility that cannabigerol could activate alpha2AR to reduce norepinephrine release to cardiovascular end organs to lower blood pressure. Despite this possibility, there are no reports examining cannabigerol cardiovascular effects. In this study, we tested the hypothesis that acute cannabigerol administration lowers blood pressure. Blood pressure was assessed via radiotelemetry at baseline and following intraperitoneal injection of cannabigerol (3.3 and 10 mg/kg) or vehicle administered in a randomized crossover design in male C57BL/6J mice. Acute cannabigerol significantly lowered mean blood pressure (-28±2 mmHg with 10 mg/kg versus -12±5 mmHg vehicle, respectively; p=0.018), with no apparent dose responsiveness (-22±2 mmHg with 3.3 mg/kg). The depressor effect of cannabigerol was lower in magnitude than the alpha2AR agonist guanfacine and was prevented by pretreatment with the alpha2AR antagonist atipamezole. These findings suggest acute cannabigerol lowers blood pressure in phenotypically normal mice likely via an alpha2AR mechanism, which may be an important consideration for therapeutic cannabigerol administration.